Genome-wide association study reveals novel QTLs and candidate genes for panicle number in rice - Guo, Jiangfan; Wang, Wenbin; Li, Wei (Frontiers in Genetics, 2024)
IntroductionPanicle number (PN) is one of the three key yield components in rice, maintaining stable tiller and PN is a crucial characteristic of an ideal plant architecture. Understanding the molecular mechanisms underlying PN is essential for breeders aiming to improve rice yield.MethodsTo dissect the genetic architecture of panicle number, a genome-wide association study (GWAS) was conducted in 411 japonica rice varieties. GWAS analysis was carried out with the mixed linear model using 743,678 high-quality SNPs.ResultsOver two experimental years, we detected a total of seven quantitative trait loci (QTLs), located on chromosomes 1, 4, 6, 8, 11, and 12; notably, qPN1.1 and qPN8 were detected consistently in both years. By combining haplotype and expression analyses, OsCKX11 was identified as the candidate gene for qPN8, while LOC_Os01g07870 and LOC_Os01g07950 were identified as candidate genes for qPN1.1. Significant differences were observed among the haplotypes of these candidate genes. Additionally, qRT-PCR results showed that LOC_Os01g07870 expression levels were significantly lower in accessions with high panicle numbers compared to those with low panicle numbers.DiscussionTo understand the natural biological function of these candidate genes, further research involving overexpression or silencing in rice is needed. Despite these challenges, our results will lay the foundation for further study of panicle development and provide valuable genetic resources for developing high-panicle-number rice cultivars using genetic engineering and molecular breeding.